Indonesia's Cosmetics Industry Attractiveness, Competitiveness and Critical Success Factor Analysis - Michelle Ferdinand; Wakhid Slamet Ciptono (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: This research aims to assess attractiveness, identify national competitiveness drivers, and critical success factors of Indonesia's cosmetics industry as Indonesia has an enormous growing market for cosmetics, but the revenue growth has been declining. Design/Methods/Approach: This research uses quantitative and qualitative data to conduct a descriptive case study. The first step of the analysis is a pre-test using quantitative data gathered through a survey questionnaire to 30 cosmetics industry practitioners to ensure the validity and reliability of the statement used in this research. The second step is an in-depth interview with ten managers in top cosmetics industry firms in Indonesia. Findings: It is shown that the cosmetics industry attractiveness in Indonesia is medium. Demand and factor conditions are the main driver of industry competitiveness. Strategy, structure, rivalry, and related and supporting industries are the supporting driver of cosmetics industry competitiveness in Indonesia. Finally, product, marketing, and speed are critical success factors in the cosmetics industry in Indonesia. Originality: A current study of Indonesia's cosmetics industry mostly explained cosmetics market size, share, growth, segments, trend, industry forecast, leading players in the industry and customer behaviour. However, the study of Indonesia's cosmetics competitiveness landscape and industry critical success factor is still limited.